A new measure of health motivation influencing food choices and its association with food intakes and nutritional biomarkers in European adolescents. Issue 4 (20th March 2021) - Santos, Thanise Sabrina Souza; Julián, Cristina; Vincenzi, Silvana Ligia; de Andrade, Dalton Francisco; Slater, Betzabeth; de Assis, Maria Alice Altenburg; Kafatos, Anthony; de Henauw, Stefaan; Gottrand, Fréderic; Androutsos, Odysseas; Kersting, Mathilde; Sjöström, Michael; et al.
Abstract: Objective: To develop a scale to assess health motivation influencing food choices and to explore its performance in the associations with food intakes and nutritional biomarkers. Design: Psychometric study using cross-sectional self-report questionnaires and nutritional biomarkers. Setting: Multi-centre investigation conducted in ten European cities. Participants: 2954 adolescents who were included in the HELENA study and completed the Food Choices and Preferences (FCP) questionnaire. Results: Nineteen out of 124 items of the FCP questionnaire were in the same dimension. Sixteen presented adequate parameters for the Scale of evaluatiOn of Food choIcEs (SOFIE). The scores were positively associated with the intakes of cereals, dairy products, meats and eggs, and fish, as well as with blood concentrations of vitamin C, β-carotene, n -3 fatty acids, cobalamin, holo-transcobalamin and folate; scores were negatively associated with the intake of alcohol. Conclusions: SOFIE can improve the assessment of motivation influencing food choices based on items with the best performance and is proposed as a new measure to health-related studies.